Vogt-Koyanagi-Harada syndrome - Hammer, H; Janáky, M; Süveges, I (Acta ophthalmologica, 1993)
The case history is presented of a 40-year-old White women with the Vogt-Koyanagi-Harada syndrome, who was successfully treated with a combination of low-dose prednisolone and cyclosporine. A. Cellular and humoral hypersensitivity to uveal and retinal antigens were demonstrated in the patient.